2011
DOI: 10.2478/v10045-011-0049-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of Mesotrione Plus Nicosulfuron with Additives as Tank Mixtures Used for Weed Control in Maize (Zea Mays L.)

Abstract: The evaluation of the effects of grass and broadleaf weed control with different mixture rates of mesotrione plus nicosulfuron with methylated rapeseed oil and urea-ammonium nitrate liquid fertilizer (UAN) applied postemergence in maize was conducted in field experiments during the agricultural seasons of 2006, 2007 and 2008. Contact angle and surface tension were measured for all tank-mix solutions. There was no phytotoxicity observed on maize following the application of the herbicide-plus-additives treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Furthermore, the number of weeds in plots treated with herbicides in 2015 was higher due to the dominance of Chenopodium album and Amaranthus retroflexus. However, Amaranthus retroflexus and Chenopodium album have been reported in previous studies as dominant weed species in maize crop Mehmeti et al (2012), as well as Chenopodium album (Skrzypczak et al, 2011). Nurs et al (2007) reported that the efficacy of foramsulfuron is strongly influenced by weed species sensitivity.…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, the number of weeds in plots treated with herbicides in 2015 was higher due to the dominance of Chenopodium album and Amaranthus retroflexus. However, Amaranthus retroflexus and Chenopodium album have been reported in previous studies as dominant weed species in maize crop Mehmeti et al (2012), as well as Chenopodium album (Skrzypczak et al, 2011). Nurs et al (2007) reported that the efficacy of foramsulfuron is strongly influenced by weed species sensitivity.…”
Section: Resultsmentioning
confidence: 95%
“…Th e tank mixture of mesotrione with s-metolachlor and mesotrione with terbuthylazine were also eff ective. All of the above mentioned active ingredients are well known in corn weed management, and they are still being tested in fi eld experiments for diff erent application methods (James et al 2006;Whaley et al 2009;Skrzypczak et al 2011;Andr et al 2014;Radivojevic et al 2014). For example, meso trione, chemically derived from a natural phytotoxin obtained from the Callistemon citrinus plant, is eff ective for preand post-emergence control of weeds in corn.…”
Section: Discussionmentioning
confidence: 99%
“…Forestry 2014; 87, 407 -415, doi:10.1093/forestry/cpt060 Advance Access publication 2 January 2014 imazamox and tribenuron-methyl in the suppression of broadleaf weeds in the regeneration of pedunculate oak forests. Nicosulfuron and tribenuron-methyl are a group of post-emergent herbicides that contain sulphonylurea herbicide and act by inhibiting the enzyme acetolactate synthase (O'Sullivan et al, 2000;Skrzypczak et al, 2011;Filimon et al, 2011). Like other sulfonylurea herbicides, nicosulfuron and tribenuron-methyl are active at low rates, have low potential for ground water contamination and have low mammalian toxicity, characteristics that are desirable for herbicides used in an integrated weed management system (O'Sullivan and Bouw, 1998).…”
Section: Forestryani Nternational Journal Of Forest Researchmentioning
confidence: 99%